2018
DOI: 10.1007/s40487-018-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Cxbladder Monitor for Patients with a History of Urothelial Carcinoma: A Physician–Patient Real-World Clinical Data Analysis

Abstract: Introduction: International guidelines advocate regular surveillance of patients following urothelial carcinoma (UC). A validated molecular diagnostic non-invasive urine test, Cxbladder Monitor, correctly identifies patients with a UC history who have low-probability of recurrence. The present study assesses the clinical utility of Cxbladder Monitor in reducing the number and frequency of urologic procedures ordered without missing detection of recurrent UC. Methods: Data from 828 physician-patient assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The total number of requested invasive procedures was reduced from 425 to 379 (−11%) following disclosure of Cxbladder information. Another study obtained the same results—a reduction in the number of total and invasive procedures [ 106 ]. The CxBladder detect assay is FDA approved.…”
Section: Urine Dna/rna Based Assaysmentioning
confidence: 60%
“…The total number of requested invasive procedures was reduced from 425 to 379 (−11%) following disclosure of Cxbladder information. Another study obtained the same results—a reduction in the number of total and invasive procedures [ 106 ]. The CxBladder detect assay is FDA approved.…”
Section: Urine Dna/rna Based Assaysmentioning
confidence: 60%
“…Cxbladder® Monitor is commercially available that can be used to test recurrent urothelial carcinoma by detecting mRNA level of five urine mRNA biomarkers IGF, HOXA, MDK, CDC , and IL8R gene expression along with few clinical variables. The overall sensitivity of 91% and a negative predictive value of 96% within 95% CI was observed for this assay and had reduced sensitivity of 86% for low-grade Ta (54, 60).…”
Section: Urine Molecular Biomarkers For Precision Medicinementioning
confidence: 82%
“…They found that 77.8% of patients were safely managed by only one cystoscopy every 2 years, reducing the total number of annual cystoscopies by 39%. This was reflected in a real world data analysis identifying this advantage of CxBM in clinical practice to have driven its increased utility ( 76 ).…”
Section: Gene-related Biomarkersmentioning
confidence: 99%